Habitat Suitability Modeling of Bornean Orangutan (Pongo pygmaeus pygmaeus) in Betung Kerihun National Park, Danau Sentarum and Corridor, West Kalimantan - Hari Prayogo; Achmad Machmud Thohari; Dedy Duryadi Solihin; Lilik Budi Prasetyo; Jito Sugardjito (Jurnal Manajemen Hutan Tropika, 2014)
Conservation areas such as national parks became the last safe area for biodiversity in Indonesia, especially for orangutan, because they have permanent status, and other forest areas may change at any time. Currently, there have been tremendous numbers of land use changes in orangutan habitats such as the development of roads, large scale plantations, settlements, farming as well as logging.  However, the available national parks still offer secure places for orangutans. This research was conducted to study the impact of spatial land use policy on the habitat distribution of orangutans. A remote sensing technology was used to study the habitat distribution and suitability of orangutan in Betung Kerihun National Park (BKNP), Danau Sentarum National Park (DSNP) and a corridor which connects these 2 parks. Seven parameters have been observed to characterize the habitat of orangutans. Habitat suitability levels of three research sites i.e. BKNP, corridor, and DSNP were 53.72%, 42.94%, and 3.34% which is considered as high, moderate, and low level of habitat suitability, respectively. These results were obtained with 93.63% of validation.